Emoční stavy matek při aplikaci Vojtovy reflexní terapie - Kastnerová, Drahomíra (Jihočeská univerzita, 2012)
V bakalářské práci se zabývám využitím Vojtovy terapie při léčbě dětí s různým stupněm motorického postižení, od nejlehčího až po dětskou mozkovou obrnu (DMO) a dále tím, jak na postižení dítěte a nutnost intenzivního cvičení reaguje matka. Vojtův princip je považován za nejúčinnější způsob léčení těchto dětí, Jako hlavní cíl práce jsem si stanovila evaluaci efektivity léčby právě dle Vojty a zjištění vývoje emotivity matky v průběhu léčby. Respondenty bylo třicet matek dětí ve věku do 18 měsíců, které docházejí na cvičení do mé ordinace. V teoretické části popisuji skutečnosti týkající se Vojtovy metody a rehabilitace dětí, které zahrnují etiologii, symptomy, klinický obraz, diagnostiku, prevenci, samotnou terapii a úlohu rodiny a matky v péči o dítě s handicapem. Praktická část se metodologicky opírá o principy kvantitativního výzkumu, který byl založen na sekundární analýze dat a přímém pozorování. Jako prostředek ke splnění dílčího cíle práce, tedy pro analýzu emocí matek při terapii dítěte dle Vojty jsem použila dva dotazníky, Zungův sebeposuzovací dotazník úzkosti a dotazník vlastní konstrukce. Kineziologické vyšetření spontánní hybnosti, kvality a kvantity tělesné postury při vývoji vzpřimovacích mechanismů potvrdilo objektivní zlepšení u dětí po třech měsících aplikace terapie dle Vojty. Jako příklad uvádím jednu kazuistiku. Z mého výzkumu vyplynulo, že míra úzkosti matek se po třech měsících cvičení dítěte Vojtovou metodou snížila. Na efektivitu terapie dle Vojty mají též vliv jisté aspekty, mezi něž patří frekvence, intenzita, včasnost zahájení terapie, správné vedení rodičů fyzioterapeutem a jejich přístup k terapii. First name and surname of the author: Drahomíra Kastnerová Title of the baccalaureate thesis: The Emotional Expression of Mother in connection with application of Vojta Therapy Department: Department of Health Education, Pedagogical Faculty, University of South Bohemia in České Budějovice Supervisor of the baccalaureate thesis: Mgr. Petra Vojtová, Ph.D. Year of defense of the baccalaureate thesis: 2012 Abstract: The baccalaureate thesis deals with the use of Vojta induction therapy for the treatment of children suffering from various degrees of motor disability ranging from the mildest one up to poliomyelitis, and furthermore with how the mother responds to the child's disability and to the need of intensive exercise. The Vojta principle is understood as the most effective way of therapy in these children. The main aim of the thesis was to evaluate the treatment efficacy precisely according to Vojta, and to determine the mother's emotiveness during the treatment. The respondents included thirty mothers of children in the age up to 18 months that came to my office for exercises. The theoretic part describes facts related to this paediatric disease, which include etiology, its symptoms, clinical image, diagnostics, prevention, the treatment itself, and the role of the family and the mother in caring for the disabled child. In terms of methodology, the practical part is supported by the principles of qualitative- quantitative research based on secondary data analysis and direct observation. Two questionnaires were used as the means to complete a partial goal of the thesis, thus to analyze the mothers' emotions during the child's therapy according to Vojta - Zung Anxiety Self-Assessment Scale and my own questionnaire. Kinesiological assessment of spontaneous motility, of the quality and quantity of physical posture in the development of stand up mechanisms confirmed objective improvement in all respondents after the therapy according to Vojta, which is evidenced by the case report attached. The research indicated reduced anxiety levels of the mothers after three months of exercises with the child using the Vojta method. Certain aspects, which include the freq
The Emotional Expression of Mother in connection with application of Vojta Therapy.
Keywords: Vojtova metoda; reflexní lokomoce; léčebná rehabilitace; psychomotorický vývoj; emoce; Zungův dotazník; Vojta Method; reflection locomotion; therapeutic rehabilitation; psychomotor development; emotions; Zung`s Questionary